HUBUNGAN PERILAKU SISWI DENGAN EFEK PENGGUNAAN KOSMETIKA YANG DITIMBULKAN DI SMAN 8 BANDA ACEH - Elfa Wardani Fitri; Surya Nola (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: Cosmetics Cosmetics is a ready-to-use dosage or active ingredient on the skin, hair, nails, lips, teeth, oral cavity for cleansing purposes, adds charm, changes appearance, protects it in good condition, body but not intended to treat or cure an illness. The use of cosmetics in the long term or excess can be bad for skin health, especially those who want quick results and do not know how to use good and true cosmetics. Thus research is needed to study the relationship of student behavior in choosing and using cosmetics with negative effects. Purpose: This study aims to study the level of knowledge, attitudes, interests, and actions of young women about cosmetics, the perception of young women in SMAN 8 Banda Aceh about the risk of exposure to harmful cosmetics and the effects caused and the behavior of choosing and using cosmetics. Methods: This was an analytical descriptive study to describe the level of female adolescent knowledge about cosmetics and to analyze the effects of cosmetic use with Cross Sectional approach. The study was conducted at SMAN 8 Banda Aceh. The population in this study were all students of class X and XI SMAN 8 Banda Aceh which amounted to 223 students. Sampling in this study using Random Sampling that produces a total of 68 respondents. then distributed questionnaires to students. Result: The correlation between cosmetic use behavior and the resultant effect The result obtained in p value 0.025 is at asymp.sig 0.05 which means Ho is rejected. Which means there is a significant relationship between attitudes with negative effects caused. Conclusion: the existence of external factors such as the use of wrong cosmetics, genetic, unhealthy lifestyle, and environmental factors can disrupt the physiology of the skin. To the drug and food regulatory agency (BPOM) is expected to be more strict in the supervision of products circulating in the marke.Keywords: behavior of choosing and using cosmetics, beauty concepts, harmful cosmetics, effects